Childhood infectious diseases and risk of multiple myeloma: an analysis of the Italian multicentre case-control study. Issue 12 (30th May 2018) - Stagnaro, E.; Parodi, S.; Costantini, A. Seniori; Crosignani, P.; Miligi, L.; Nanni, O.; Piro, S.; Ramazzotti, V.; Rodella, S.; Tumino, R.; Vindigni, C.; Vineis, P.
Abstract: Common childhood infectious diseases have been associated with a reduced risk of following haematopoietic malignancies, but investigations on multiple myeloma (MM) are scarce. Information about 213 MM cases and 1128 healthy controls were obtained from a multicentre population-based Italian case-control study. The association between chickenpox, measles, mumps, pertussis and rubella and the MM risk was estimated by unconditional logistic regression, adjusting for age, gender and residence area. No association was found between MM risk and any considered infectious disease. The number of infections was slightly inversely associated with the risk of MM, but statistical significance was not reached (OR 0.87, 95% CI 0.55–1.4 for 1-2 diseases vs. none and OR 0.68, 95% CI 0.41–1.1 for 3-5 diseases, respectively, P = 0.131). We did not find a clear evidence that common infections during childhood are associated with the subsequent risk of developing MM.